2011
DOI: 10.1177/0022343310397404
|View full text |Cite
|
Sign up to set email alerts
|

Poverty, minority economic discrimination, and domestic terrorism

Abstract: Recognizing that the empirical literature of the past several years has produced an inconclusive picture, this study revisits the relationship between poverty and terrorism and suggests a new factor to explain patterns of domestic terrorism: minority economic discrimination. Central to this study is the argument that because terrorism is not a mass phenomenon but rather is undertaken by politically marginal actors with often narrow constituencies, the economic status of subnational groups is a crucial potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
237
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(253 citation statements)
references
References 58 publications
11
237
1
4
Order By: Relevance
“…Piazza's statistical analysis of 172 countries between 1970 and 2006 found a link between minority groups' experience with economic discrimination and higher rates of domestic terrorism. 21 Victoroff et al similarly found a link between a sense of discrimination and support for suicide bombings among Muslims residing in the West. Analyzing two sets of Pew survey data of a combined 2,677 adult Muslim residents in Europe and the United States, they concluded "that younger age and perceived discrimination toward Muslims living in the West are significantly associated with the attitude that suicide bombing is justified."…”
Section: Integration Deficitmentioning
confidence: 95%
“…Piazza's statistical analysis of 172 countries between 1970 and 2006 found a link between minority groups' experience with economic discrimination and higher rates of domestic terrorism. 21 Victoroff et al similarly found a link between a sense of discrimination and support for suicide bombings among Muslims residing in the West. Analyzing two sets of Pew survey data of a combined 2,677 adult Muslim residents in Europe and the United States, they concluded "that younger age and perceived discrimination toward Muslims living in the West are significantly associated with the attitude that suicide bombing is justified."…”
Section: Integration Deficitmentioning
confidence: 95%
“…New factors, such as minority discrimination [39], and economic sanctions [40] are related to persons being more likely to participate in terrorism, as opposed to poverty. Choi et al [39], found a significant relationship between economic discrimination against minority communities which may have increased hardships for the poor in terrorist-active nations, increasing grievances.…”
Section: Literature Reviewmentioning
confidence: 99%
“…83 Poverty or socioeconomic disadvantages become markedly more potent motivational preconditions for terrorism when they overlap with intergroup inequality. 84 A 2005 report on the integration of minorities in the Netherlands indicated that non-Western immigrants and their children were socioeconomically disadvantaged compared to the indigenous population. For instance, they had lower educational qualifications, were more likely to be unemployed, earned less income, underperformed at school, and were disproportionally represented in statistics on crime.…”
Section: (Relative) Deprivation and Intergroup Inequalitymentioning
confidence: 99%